1982
DOI: 10.3758/bf03327018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lateral and medial septal lesions on response suppression maintained by response-contingent and response-independent shock

Abstract: Rats with electrolytic lesions in the medial (MS) or lateral (LS) septal areas were allocated to groups on electrophysiological criteria (loss or persistence of hippocampal theta rhythm, respectively) subject to subsequent histological checking. They were trained to press a lever for sucrose reward on a random interval (RI) schedule and while leverpressing were presented with two stimuli, each associated with a different schedule of shock delivery: in the presence of one, shocks occurred on an RI schedule irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In the present multiple FI-RI study, rats with medial septal lesions had higher response rates than did controls on the RI 4O-sec component. This agrees with the findings of Feldon, Rawlins, and Gray (1982), who also found that medial septal lesions resulted in higher response rates on a RI 64sec reinforcement schedule. In comparing the components of the multiple schedule of reinforcement, it was evident that rats with lateral or medial septal lesions responded differently when the FI or RI schedules of reinforcement were in effect.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present multiple FI-RI study, rats with medial septal lesions had higher response rates than did controls on the RI 4O-sec component. This agrees with the findings of Feldon, Rawlins, and Gray (1982), who also found that medial septal lesions resulted in higher response rates on a RI 64sec reinforcement schedule. In comparing the components of the multiple schedule of reinforcement, it was evident that rats with lateral or medial septal lesions responded differently when the FI or RI schedules of reinforcement were in effect.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with several studies that suggest that the medial and lateral septum may act in opposition to each other in a variety of behavioral settings. For instance, rats with medial septal lesions have larger social contact times (Poplawsky & Johnson, 1973), show more shock-induced suppression of a barpress response (Feldon et al, 1982;Poplawsky & Hoffman, 1979), and take longer to extinguish a straight alley running behavior (Feldon & Gray, 1979a, 1979b than rats with lateral septal lesions. Changes in response rates and other behaviors not only are a function of the anatomical loci of the septal damage, but also may change as a function of postoperative training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion, taken together with the lack of differentiation of medial and lateral septal lesion effects in DRL tasks (Brookes et al, 1983), emphasizes that this behavioral task cannot discriminate between sites of septo-hippocampal system damage, being apparently equally sensitive to all. Given that double dissociations have previously been demonstrated between some of the lesions that DRL does not differentiate (e.g., Feldon, Rawlins, & Gray, 1982;Gray, Feldon, Rawlins, Owen, & McNaughton, 1978;Poplawsky & Hoffman, 1979), it seems possible that there may be multiple causes of DRL impairments following damage in this system. The results of the drug experiment may be taken to support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have made clear that the septohippocampal system is not functionally homogeneous throughout. Lateral and medial septallesions produce different results on a variety of measures, including be-havioral suppression (Feldon et al, 1982) and hippocampal theta activity (Rawlins, Feldon, & Gray, 1979). There are also differences in the effects of stimulation of the lateral and medial septum.…”
Section: Unit Recordingmentioning
confidence: 99%